Dynamics of Fat Cells of the Bronchial Tree Mucosa in Postnatal Ontogenesis - Sultonov, Ravshan Komiljonovich; Sodiqova, Zumrat Shavkatovna; o’g’li, Boboyorov Sardor Uchqun (Central Asian Journal of Medical and Natural Science, 2021)
Тhis article was aimed at studying the structure of different densities of fat cells in the mucous membranes of the bronchi tree in the stage of postnatal ontogenesis in children under three years of age and the examination was carried out. Fat cells in children under the age of one year are 10-12 µm, and with age, they also grow and divide into large, medium and small fat cells. The number and types of fat cells in the mucous membrane of the bronchi of the Bee, which the child has grown in age, have increased to the age of 3 years, and the main part is made up of 2-type cells.